Accuracy evaluation of classical integer order and direct non-integer order based numerical algorithms of non-integer order derivatives and integrals computations - Brzezinski, Dariusz W.; Ostalczyk, Piotr (2014 Federated Conference on Computer Science and Information Systems, 2014)
In this paper the authors evaluate in context of numerical calculations accuracy classical integer order and direct non-integer based order numerical algorithms of non-integer orders derivatives and integrals computations. Classical integer order based algorithm involves integer and fractional order differentiation and integration operators concatenation to obtain non-integer order. Riemann-Liouville and Caputo formulas are applied to obtain directly derivatives and integrals of non-integer orders. The following accuracy comparison analysis enables to answer the question, which algorithm of the two is burdened with lower computational error. The accuracy is estimated applying non-integer order derivatives and integrals computational formulas of some elementary functions available in the literature of the subject.